EFEKTIVITAS PEMBERIAN MEDIA TANAM DAN POC CANGKANG TELUR DALAM PENINGKATAN KESUBURAN TANAH PADA STEK TANAMAN ANGGUR (Vitis vinifera) DI PRE NURSERY - Monica, Cici; Tarigan, Ruth Riah Ate; Lubis, Najla (Agros Journal of Agriculture Science, 2024)
The aim of this research was to determine the effectiveness of providing planting media and eggshell poc in increasing soil fertility on grape plant (vitis vinifera) cuttings in the pre-nursery and their interactions. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were needed in the study. The first factor examined was the treatment of planting media with the symbol "C" consisting of C0 = 0 kg/ plot, C1 = 1 top soil: 1 rice husk/ plot, C2 = 2 top soil: 1 rice husk/ plot, C3 = 1 top soil: 2 rice husks/plot. Factor II treatment of giving eggshell POC with symbol I consists of I0 = 0 mL/liter of water/plot, I1 = 5 mL/liter of water/plot, I2 = 10 mL/liter of water/plot. The parameters observed were plant height (cm), tendril length (cm), number of leaves (strands), number of stem segments, stem diameter (mm) and number of tendrils. The results of the research showed that the provision of planting media, eggshell liquid organic fertilizer and the second interaction showed an insignificant effect on all parameters, namely plant height (cm), tendril length (cm), number of leaves (strands), number of stem segments, stem diameter ( mm) and number of tendrils. Key words: planting media, eggshell liquid organic fertilizer, grape plants INTISARITujuan penelitian ini adalah untuk mengetahui efektivitas pemberian media tanam dan poc cangkang telur dalam peningkatan kesuburan tanah pada stek tanaman anggur (vitis vinifera) di pre nursery berserta  interaksinya. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK)  Faktorial terdiri dari 2 faktor dengan 12 kombinasi perlakuan dan 3 ulangan sehingga diperlukan 36 plot dalam penelitian. Faktor yang pertama diteliti adalah perlakuan media tanam dengan simbol “C” terdiri dari C0= 0 kg/ plot, C1 = 1 top soil : 1 sekam padi/plot, C2 = 2 top soil : 1 sekam padi/plot, C3 = 1 top soil : 2 sekam padi/plot. Faktor II perlakuan pemberian POC  cangkang telur dengam simbol I terdiri I0 = 0 mL/liter air/Plot, I1 = 5 mL/liter air/plot, I2 = 10  mL/liter air/plot. Adapun parameter yang diamatin adalah Tinggi Tanaman (cm), panjang sulur  (cm), jumlah daun (helai), jumlah ruas batang, diameter batang (mm) dan jumlah sulur. Hasil  penelitian menunjukan bahwa pemberian media tanam, pupuk organik cair cangkang telur dan  interaksi kedua menunjukan pengaruh yang tidak nyata pada semua parameter yaitu Tinggi  Tanaman (cm), panjang sulur (cm), jumlah daun (helai), jumlah ruas batang, diameter batang  (mm) dan jumlah sulur. Kata kunci: media tanam, pupuk organik cair cangkang telur, tanaman anggur